Common and Rare Genetic Variants That Could Contribute to Severe Otitis Media in an Australian Aboriginal Population. (9th March 2021) - Jamieson, Sarra E; Fakiola, Michaela; Tang, Dave; Scaman, Elizabeth; Syn, Genevieve; Francis, Richard W; Coates, Harvey L; Anderson, Denise; Lassmann, Timo; Cordell, Heather J; Blackwell, Jenefer M
Abstract: Background: Our goal was to identify genetic risk factors for severe otitis media (OM) in Aboriginal Australians. Methods: Illumina ® Omni2.5 BeadChip and imputed data were compared between 21 children with severe OM (multiple episodes chronic suppurative OM and/or perforations or tympanic sclerosis) and 370 individuals without this phenotype, followed by FUnctional Mapping and Annotation (FUMA). Exome data filtered for common (EXaC_all ≥ 0.1) putative deleterious variants influencing protein coding (CADD-scaled scores ≥15] were used to compare 15 severe OM cases with 9 mild cases (single episode of acute OM recorded over ≥3 consecutive years). Rare (ExAC_all ≤ 0.01) such variants were filtered for those present only in severe OM. Enrichr was used to determine enrichment of genes contributing to pathways/processes relevant to OM. Results: FUMA analysis identified 2 plausible genetic risk loci for severe OM: NR3C1 (Pimputed_1000G = 3.62 × 10 −6 ) encoding the glucocorticoid receptor, and NREP (Pimputed_1000G = 3.67 × 10 −6 ) encoding neuronal regeneration-related protein. Exome analysis showed: (i) association of severe OM with variants influencing protein coding (CADD-scaled ≥ 15) in a gene-set ( GRXCR1, CDH23, LRP2, FAT4, ARSA, EYA4 ) enriched for Mammalian Phenotype Level 4 abnormal hair cell stereociliary bundle morphology and related phenotypes; (ii) rare variants influencing protein coding only seen in severe OM provided gene-sets enriched for "abnormal ear" ( LMNA, CDH23, LRP2, MYO7A, FGFR1 ), integrin interactions, transforming growth factor signaling, and cell projection phenotypes including hair cell stereociliary bundles and cilium assembly. Conclusions: This study highlights interacting genes and pathways related to cilium structure and function that may contribute to extreme susceptibility to OM in Aboriginal Australian children. Abstract : Genome-wide analysis identifies common noncoding putative regulatory, as well as common and rare potentially deleterious variants directly influencing protein coding, in genes and pathways related to cilium structure and function that may contribute to severe otitis media in Aboriginal Australians.